2016
DOI: 10.1101/gad.281881.116
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum: Human nonsense-mediated RNA decay initiates widely by endonucleolysis and targets snoRNA host genes

Abstract: targets snoRNA host genes Human nonsense-mediated RNA decay initiates widely by endonucleolysis and License Service Email Alerting click here. right corner of the article or Receive free email alerts when new articles cite this article-sign up in the box at the top

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…( Fafard-Couture et al 2021 ). These two abundance classes are mainly regulated by the presence or absence of a dual-initiation promoter within the host gene, which, combined with the nonsense-mediated decay (NMD) pathway, allows the uncoupling of snoRNA and host gene expression ( Lykke-Andersen et al 2016 ; Nepal et al 2020 ; Fafard-Couture et al 2021 ). Furthermore, we and other groups have shown that the abundance of most snoRNAs does not correlate well with that of their host gene or even between snoRNA copies, with the observation that snoRNAs embedded within the same host gene often vary extremely in terms of abundance (from not expressed to highly abundant) ( Warner et al 2018 ; McCann et al 2020 ; Bergeron et al 2021 ; Fafard-Couture et al 2021 ).…”
mentioning
confidence: 99%
“…( Fafard-Couture et al 2021 ). These two abundance classes are mainly regulated by the presence or absence of a dual-initiation promoter within the host gene, which, combined with the nonsense-mediated decay (NMD) pathway, allows the uncoupling of snoRNA and host gene expression ( Lykke-Andersen et al 2016 ; Nepal et al 2020 ; Fafard-Couture et al 2021 ). Furthermore, we and other groups have shown that the abundance of most snoRNAs does not correlate well with that of their host gene or even between snoRNA copies, with the observation that snoRNAs embedded within the same host gene often vary extremely in terms of abundance (from not expressed to highly abundant) ( Warner et al 2018 ; McCann et al 2020 ; Bergeron et al 2021 ; Fafard-Couture et al 2021 ).…”
mentioning
confidence: 99%